Cerebrovascular Dysfunction at the Intersection of Ischemia and Alzheimer's Disease. (20th December 2022) - Ismail, Ozama; Pike, Martin; Zhang, Wenri; Mishra, Anusha
Abstract: Background: Cerebrovascular dysregulation is one of the earliest detectable changes in Alzheimer's disease (AD) etiology that precedes the descent into dementia 1 . Ischemic events such as stroke and silent infarcts trigger cerebrovascular dysfunction 2, 3, accelerate cognitive decline 4 and increase dementia risk 5 . Further, the resulting decrease in cerebral blood flow (CBF) can induce the formation of amyloid β 6 . Thus, we examined cerebrovascular function at the intersection of ischemia and AD by measuring CO2 ‐evoked hyperemia and neurovascular coupling (NVC) after small strokes in wild type and Tg2576 model of AD‐related amyloidosis. Method: We established a model of small ischemic strokes by performing a short 30‐minute middle cerebral artery occlusion, yielding a mild subcortical infarct (MSCI). We performed MSCI in 6‐month old Tg2576 and littermate wild‐type mice (WT) and compared them to naïve mice. We used arterial spin‐labeling (ASL) MRI to quantify CBF and CO2 ‐evoked hyperemia at 10 and 14 months of age and Laser Doppler flowmetry (LDF) to measure NVC at 14 months of age. We also quantified hippocampal volumes. Result: There was no apparent change in hippocampal volume after MSCI in either genotype. There was a reduction in NVC in WT+MSCI mice in both hemispheres, with a trend towards greater reduction in Tg2576+MSCI mice. The CO2 ‐evoked hyperemia was also reduced in WT+MSCI and Tg2576+MSCI mice compared to WT naïves. Curiously, naïve Tg2576 mice showed the most severe impairment in CO2 ‐evoked hyperemia, which appeared improved in Tg2576+MSCI. We are re‐examining this finding. Conclusion: Using an innovative mixed model of mild ischemia and amyloidosis, here we report that the two pathologies can synergize to accelerate cerebrovascular impairments. Strikingly, we found that even a small one‐sided stroke can impair cerebrovascular function bilaterally. Future studies will determine the extent to which amyloid pathology and cognitive deficits are exacerbated by such impairments. Our findings suggest that targeting early cerebrovascular dysfunction after ischemia may prove useful in deterring the onset of dementia later in life. References : Iturria‐Medina, Y. et al. (2016) Nat. Commun . 7, 11934. Salinet, A.S.M., Robinson, T.G. & Panerai, R.B. (2015) J. Appl. Physiol . 118, 170–177. Li, Z., McConnell, H.L. & Mishra, A. (2021). Front Cell Nuerosci . 15: 762843. Levine, D.A. et al. (2015) JAMA . 314, 41–51. Vermeer, S.E., Longstreth, W.T. & Koudstaal, P.J. (2007) Lancet Neurol . 7, 611–9. Wen, Y., Onyewuchi, O., Yang, S., Liu, R. & Simpkins, J.W. (2004) Brain Res . 1009, 1–8.